2020
DOI: 10.1007/s00018-020-03679-5
|View full text |Cite
|
Sign up to set email alerts
|

New inhibitor targeting Acyl-CoA synthetase 4 reduces breast and prostate tumor growth, therapeutic resistance and steroidogenesis

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Nature Switzerland AG. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…While we did not detect any impact on c-Myc protein levels (data not shown), other ACSL4-dependent processes cannot be excluded. For example, ACSL4 contributes to de novo steroid synthesis, and chemical inhibition of ACSL4 was reported to reduce tumor growth in steroid-dependent models of breast and prostate cancer [ 48 ]. Consequently, future investigations should aim to dissect the relative contribution of ferroptosis-dependent and ferroptosis-independent roles of ACSL4 in promoting liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not detect any impact on c-Myc protein levels (data not shown), other ACSL4-dependent processes cannot be excluded. For example, ACSL4 contributes to de novo steroid synthesis, and chemical inhibition of ACSL4 was reported to reduce tumor growth in steroid-dependent models of breast and prostate cancer [ 48 ]. Consequently, future investigations should aim to dissect the relative contribution of ferroptosis-dependent and ferroptosis-independent roles of ACSL4 in promoting liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ACSL4 is overexpressed in breast cancer tissues compared with adjacent normal tissues [47] . In vitro, ACSL4 inhibition significantly suppresses cell proliferation, invasion, and migration in MDA-MB-231 cell line [ 48 , 49 ]. Taking the evidence together, aggressive biological behavior is indicated to ACSL4 overexpressed tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ACSL4 might sensitize breast cancer cells to cytotoxic drugs through promoting BCL11B and inhibiting GDF15, which requires future study to elucidate. Of note, two basic studies found ACSL4 inhibitor PRGL493 slows down breast cancer cell proliferation treated by low-dose chemotherapeutic agents, but the role of ACSL4 in chemotherapy-induced ferroptosis is to be investigated [ 48 , 52 ]. In future, ferroptosis-inducing agents may become a new therapeutic strategy in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ACSL4 expression was 0.386 times higher on average in p53-positive patients than in p53-negative individuals. Additionally, in both breast tumor cells and animal models, the use of PRGL493, a chemical inhibitor of ACSL4 impeding de novo steroid synthesis, could block cell proliferation and tumor growth, and promote the sensitivity of tumor cells to chemotherapeutic and hormonal treatment ( Castillo et al, 2021 ). It is well-known that estrogen receptor (ER) negative breast cancer is less sensitive to chemotherapy, more likely to relapse, leading to poor prognosis.…”
Section: Acyl-coa Synthetase Long-chain Family 4 and Cancermentioning
confidence: 99%
“…Researchers found lncRNAs NEAT1 could promote docetaxel-resistant prostate cancer cells proliferation and invasion by sponging miR-204-5p and miR-34a-5p, leading to an increasing expression of ACSL4 ( Jiang et al, 2020 ). And inhibitor targeting to ACSL4 could reduce prostate cancer growth, therapeutic resistance and steroidogenesis ( Castillo et al, 2021 ).…”
Section: Acyl-coa Synthetase Long-chain Family 4 and Cancermentioning
confidence: 99%